A qualitative study on the impact of bleeding disorders on the daily life of Dutch women - Tessa C. M. van Gastel; Lorynn Teela; Manon E. L. Degenaar-Dujardin; Vicky Lehmann; Marjolein Peters; Karin Fijnvandraat; Lotte Haverman (Women's Health)
Background: Despite growing awareness of the need for better healthcare and research focused on women, sex-based inequalities persist, resulting in poorer health outcomes for women. Particularly, women with congenital bleeding disorders (CBDs) receive less care, are underrepresented in research, and experience diagnostic delays compared to men with CBDs, despite both exhibiting symptoms. Objectives: To identify lived experiences and care needs of women with CBDs. Design: A qualitative study, including focus groups and semi-structured interviews. Methods: Women were eligible to participate if they were between 18 and 40 years old, diagnosed with a CBD, and able to speak Dutch. Focus groups or semi-structured interviews about the themes (1) healthcare, (2) social functioning, (3) work and education, and (4) sexuality and intimacy were conducted in person or online, based on women’s preference. Thematic analysis was conducted in MAXQDA. Results: Twenty-eight women with a CBD participated. In general, as well as in primary healthcare settings, women experienced a lack of knowledge among healthcare providers and a tendency to downplay their symptoms. Furthermore, the women expressed limited awareness among healthcare professionals (HCPs) regarding the impact of CBDs on mental health, particularly during specific life phases (e.g., transition to high school). Women described the need to schedule social activities around their menstruation cycle and emphasized how heavy and prolonged menstrual bleeding negatively affected their work and education. Feelings of insecurity and shame were reported, primarily related to menstruation. Additionally, insecurity due to bruises and bleeding affects women’s sexuality. Lastly, a lack of information regarding pregnancy and delivery was reported. Conclusion: Improved symptom recognition and a better understanding of the impact of CBDs on the daily life and mental health of women is needed. Accessible informational materials for both women and HCPs, as well as platforms for sharing experiences, may help facilitate this process.